Big data aplication for selecting theses topics (2019)
The chairs of thesis research in Computer Sciences at the University of Mumbai, in India, have different tools that provide academic support to those who begin the course. Students present difficulty in selecting the topic to study and, in some cases, this is a reason to neglect or delay in the career. Having a registry of thesis of the graduates proved to be useful for obtaining patterns on the relationship between the research area addressed in this thesis and the characteristics that define the researcher. For this study, the knowledge discovery process in Database was used. Finally, the results of the use of algorithms J4.8 in WEKA, ID3 tags in RapidMiner and CART IN Knime and the various models generated, with the data collected were presented.